2021
DOI: 10.1002/emp2.12398
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and management of urethral foreign bodies and description of a novel ultrasound‐guided catheter‐based extraction technique

Abstract: There are numerous reports in the medical literature documenting urethral foreign bodies with nearly all cases found in men and often associated with underlying psychiatric disorders, autoerotic stimulation, and/or intoxication. Patients most commonly presented with localized penile pain, hematuria, dysuria, and occasionally obstruction. Although endoscopic removal by a urologist is often the first‐line treatment, this report describes evaluation and management considerations and presents a novel extraction te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Note the location, size, orientation, and relationship of the object to the surrounding organ as they are essential for the planning of extraction. [1,4] While manual milking might be possible in distal-located objects-as Palmer et al [2] discovered that 54% of urethral foreign objects located in distal urethra were successfully evacuated by manual milking and 20% cases were able to evacuate the foreign bodies during voiding-we found that the wire-like object in our patient was located in his prostatic urethra. Therefore, we decided to perform urethroscopy while also being ready for an open surgery should the urethroscopy procedure fail to extract all the beads.…”
Section: Discussionmentioning
confidence: 49%
“…Note the location, size, orientation, and relationship of the object to the surrounding organ as they are essential for the planning of extraction. [1,4] While manual milking might be possible in distal-located objects-as Palmer et al [2] discovered that 54% of urethral foreign objects located in distal urethra were successfully evacuated by manual milking and 20% cases were able to evacuate the foreign bodies during voiding-we found that the wire-like object in our patient was located in his prostatic urethra. Therefore, we decided to perform urethroscopy while also being ready for an open surgery should the urethroscopy procedure fail to extract all the beads.…”
Section: Discussionmentioning
confidence: 49%
“…Although the exact incidence of repeated offenders is unknown, it is more common among incarcerated and institutionalised individuals or in the setting of psychosis and intoxication. 14,18 Simms et al reported the case of a 50-year-old male who had presented with more than 40 encounters of urethral foreign body insertion in a setting of intoxication and/or psychosis. The repeated episodes of foreign body insertion into the urethra ultimately resulted in a urethral defect at the penoscrotal junction.…”
Section: Discussionmentioning
confidence: 99%
“…Under real-time ultrasound visualisation, the catheter and inflated balloon were slowly withdrawn, guiding the foreign body distally and to exit the urethral meatus. 14 If these manoeuvres are unsuccessful, endoscopic removal with the help of biopsy forceps or stone baskets is an alternative option. Open surgery should be considered a last resort.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 These objects come in a wide array, including surgical sounds, household items (speaker wire, AAA batteries, open safety pins, a plastic cup, straws, marbles, razors, plastic utensils) plants, and various fluids. 3 , 4 Little is known about the epidemiology of sounding, possibly due to a real or perceived stigma. One study investigating a population of 2122 men who have sex with men (MSM) reported that 10.7 % of participants had engaged in sounding at some point in their lifetime.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Bacteria from unsterilized inserted objects can easily cross the urethra's submucosa and enter the vasculature of the corpus spongiosum. 4 Long-term sounding may lead to abscesses, calculus formation, urethral diverticula, strictures, or fistula formation. 1 , 6 …”
Section: Introductionmentioning
confidence: 99%